Macular hole formation after macular haemorrhage associated with rupture of retinal arterial macroaneurysm. Issue 10 (10th June 2009) - Sagara, N; Kawaji, T; Koshiyama, Y; Inomata, Y; Fukushima, M; Tanihara, H
Abstract : Aim: To investigate the frequency and risk factors of macular hole (MH) formation after rupture of a retinal arterial macroaneurysm. Methods: Fifty-six eyes from 56 patients with rupture of a retinal arterial macroaneurysm with or without an MH (MH and non-MH groups, respectively) were reviewed. Frequency and risk factors related to MH formation were assessed, with risk factors including age; sex; distance from the macroaneurysm to the fovea; incidence of haemorrhages involving the macula such as preretinal, subinternal limiting membrane (sub-ILM), subretinal and vitreous; and vitreous surgery. MH formation in these patients was recorded and analysed. Results: Of the 56 eyes reviewed, seven (12.5%) had an MH after rupture of the retinal arterial macroaneurysm. The incidence of subretinal and sub-ILM haemorrhages involving the macula was significantly greater in the MH group than in the non-MH group (p = 0.037 and 0.045, respectively). Conclusion: These results suggest that the presence of subretinal and sub-ILM haemorrhages after rupture of a retinal arterial macroaneurysm may contribute to formation of an MH.